IMPROVING THE PERFORMANCE OF HEALTH PERSONNEL (NAKES) POST COVID-19 THROUGH TELEMEDICINE HEALTH SERVICES - Suhartini, Endeh; I, M.Dikdik; Suryani, Danu; Imantaka, Balvas; Devisa, Devisa (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Health workers are people who have expertise through formal education and training in certain scientific disciplines so that they professionally have expertise and abilities in the field of health services. After Covid-19, as health service technology develops, it becomes more advanced and develops rapidly, one of which is the professional skills possessed by health workers, which are carried out through telemedicine to meet the needs of the community quickly and precisely, especially for those who are sick. The development of telemedicine health services is growing rapidly and starting with Covid-19, people need health services during Covid-19 because of limited steps and restrictions on limited consultations to health workers, so telemedicine is the first step for electronic consultations. Telemedicine is a major revolution in the health sector which continues to develop until after Covid-19. Telemedicine continues to be carried out by the community to meet health needs so that they do not meet directly with medical personnel, just technology that makes it possible for users.